Weak deflection angle of extended uncertainty principle black holes - Kumaran, Yashmitha; Övgün, Ali (Iop Publishing Ltd, 2020)
We discuss the effects of quantum fluctuations spewed by a black hole on its deflection angle. The Gauss-Bonnet theorem (GBT) is exploited with quantum corrections through the extended uncertainty principle (EUP), and the corresponding deflection angle is obtained. Moreover, we have attempted to broaden the scope of our work by subsuming the effects of plasma medium on the deflection angle. To demonstrate the degree of difference, the acquired results are compared with the prevailing findings.
Keywords: deflection of light; gravitational lensing; massive photon; black hole; Gauss-Bonnet theorem; extended uncertainty principle; quantum gravity